Non-cancellation of the parity anomaly in the strong-field regime of QED2+1 - Ott, Robert; Zache, Torsten Victor; Berges, Jürgen (Physics letters, 2020)
Quantum fluctuations lead to an anomalous violation of parity symmetry in quantum electrodynamics for an even number of spatial dimensions. While the leading parity-odd electric current vanishes in vacuum, we uncover a non-cancellation of the anomaly for strong electric fields with distinct macroscopic signatures. We perform real-time lattice simulations with fully dynamical gauge fields and Wilson fermions in 2+1 space-time dimensions. In the static field limit, relevant at early times, we solve the problem analytically. Our results point out the fundamental role of quantum anomalies for strong-field phenomena, relevant for a wide range of condensed matter and high-energy applications, but also for the next generation of gauge theory quantum simulators.
Im Titel ist der Ausdruck "2+1" tiefgestellt
Gesehen am 13.08.2020